Aflatoxins Contamination in Maize Products from Rural Communities in San Luis Potosi, Mexico - Beatriz A. Zuki-Orozco; Lilia E. Batres-Esquivel; María D. Ortiz-Pérez; Bertha I. Juárez-Flores; Fernando Díaz-Barriga (Ubiquity Press, 2018)
Background: Aflatoxins are a group of mycotoxins that have been associated with hepatic damage and cancer. Aflatoxins B1 and B2 are secondary metabolites produced by fungi Aspergillus. These toxins can be found in a variety of commodities, especially in maize, and have been studied around the world due to their effects in human health. The Latin American population is especially exposed to aflatoxins given that maize products can be found in traditional diets all over the continent. Interestingly, in Mexico, chronic hepatic diseases and cirrhosis are leading causes of death in adult population. Methods: In order to observe the effect of physical variables like temperature and humidity, this study was conducted collecting samples in four different seasons, in two communities in the State of San Luis Potosi, in Mexico. The content of aflatoxins in tortillas was measured using immunoaffinity columns prior to HPLC-FLD analysis. Findings: Results showed that 18% of samples exceeded the Mexican limits for AFB1; whereas, 26% of the samples exceeded the limits of the European Union for AFB1. The AFB1 was detected in 80% of samples in one site and higher concentrations were found in samples collected during fall and winter seasons. Conclusions: Lack of control in storing practices is the principal cause for the contamination of maize. Considering that maize products are part of the staple diet of Mexican population, our results show that AFB1 detection has to be declared a public health priority. Detection and prevention of aflatoxins through a surveillance program, may avoid chronic health effects.